Pendayagunaan Kewirausahaan Siswa Kompetensi Keahlian Pemasaran (Studi Kasus di SMK Sudirman 1 Wonogiri) - Suwandi, Agus; , Dr. Samino, M.M; , Dra. Titik Asmawati, M.Si (2015)
This study aims to: (1) Describe the planning of Entrepreneurship Student Marketing Competency SMK Sudirman 1 Wonogiri. (2) Describe the implementation of Enterprise Reform Vocational Students Skills Competency Marketing Sudirman 1 Wonogiri. (3) Describe the Evaluation of Enterprise Reform Vocational Students Skills Competency Marketing Sudirman 1 Wonogiri. The approach used in this study is qualitative as a whole is expected to describe the object under study, analyze it so that it can be formulated for the appropriate utilization of entrepreneurship in creating young entrepreneurs. The results showed: 1) utilization of entrepreneurship held at the school is in the form of the production unit in which the management of school canteens and builders kemitrannya conducted entirely by students Competency Marketing. Being jointly managed is a Business Center and outside of school (World Business / Industrial World) through industrial visits and internship (PSG), 2) Integration of entrepreneurship into some subjects productively realized in the teaching, 3) curriculum is designed and developed tailored to stakeholders' needs. Based on the findings of the research can be concluded that training, habituation and giving responsibility through the target at the time the students implement their knowledge of the school can include businesses successful around the school and DU / DI relevant local potentials so that students can grow into wirausahawanan that reliable. Keywords: business center, reform, production unit, , PSG